SITUATING CHINESE AND INDIAN ENGAGEMENT IN AFRICA: A ‘NEW SCRAMBLE FOR AFRICA’? - Yaruingam, A.S.; Sharma, Saurabh (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Africa is often touted as the continent of opportunities. Lately, Africa has realized this potential and has been seeking to turn ‘potentiality’ into ‘actuality.’ It has been at the cusp of geopolitical changes taking place in the regional as well as global order. Governments and businesses from all around the world are rushing to strengthen diplomatic, strategic, and commercial ties. This paper limits its study to understand the role played by India and China in Africa and how it is shaping Africa as well getting shaped in the process. India and China have emerged as two great Asian powers with vibrant economy and huge demography with global ambitions. Not only does Africa offers unexplored resources to feed these rapidly growing Asian giants, it also holds immense geopolitical importance as a voting bloc of 54 countries to shape global opinion in the United Nations and elsewhere. While Africa is big enough for both these emerging powers, but there is a growing concern that the rivalry between China and India could play out to the detriment of African interests and lead to a ‘new scramble for Africa.’